Anti-sepsis protection of Xuebijing injection is mediated by differential regulation of pro- and anti-inflammatory Th17 and T regulatory cells in a murine model of polymicrobial sepsis. (30th January 2018) - Chen, Xi; Feng, Yuxin; Shen, Xiya; Pan, Guixiang; Fan, Guanwei; Gao, Xiumei; Han, Jihong; Zhu, Yan
Abstract: Ethnopharmacological relevance: Xuebijing injection (XBJ), a Chinese herbal medicine containing extracts from 5 herbs, is frequently used as an add-on with standard therapies to treat sepsis or septic shock with fewer side effects in China. Nonetheless, its mechanism of action on septic shock remains to be unveiled. We explored the differential effects of XBJ on subtypes of CD4+ T cell differentiation and septic shock protection in a murine model to understand the contribution of XBJ to regulation of the inflammation-immune axis function. Materials and methods: In vitro T cell differentiation assays were performed to determine the effect of XBJ on CD4+ regulatory T cell and T helper cell differentiation. Besides, 2 ml/kg, 6 ml/kg- and 18 ml/kg of XBJ were administered to different groups of septic mice once/day for 5 days after cecal ligation and puncture (CLP) surgeries. 36 h after CLP, serum levels of pro-inflammatory cytokine TNF-α and IL-6 were determined with Elisa. Frequencies of CD4+ T cells were analyzed after staining with Tregs and T helper cell lineage specific antibodies by flow cytometer. Results: XBJ at 18 ml/kg stimulated Treg differentiation and moderately inhibited Th17 differentiation in vitro . Accordingly, 18 ml/kg XBJ facilitated the expansion of IL-10+ Tregs and normalized pro-inflammatory Th17 population in septic mice. This regimen also significantly reduced serum levels of inflammatory cytokines TNF-α and IL-6 in septic mice. Additionally, 18 ml/kg XBJ injection effectively prevented neutrophil infiltration into the lung and kidney and improved survival in this septic shock model. Conclusions: In summary, XBJ improves survival in septic shock partially through preventing cytokine storm, inhibiting inflammation and regulating the balance of Tregs and Th17 cells. Thus, higher dose of XBJ is a potential regimen to benefit septic shock patients. Graphical abstract: